The Analysis of Digital Based Creativity and Innovation of MSMEs in Bekasi City - Santoso, Teguh; Firmansyah, Ade; Sudarwanto, Sudarwanto (Universitas Mercu Buana, 2024)
This research aims to determine the analysis of digital-based creativity and innovation of MSMEs in Bekasi City. This study is a descriptive-qualitative approach. Data collection techniques used interview, observation and documentation methods. Determination of informants based on MSME owners in Bekasi City. The results of the study indicate that digital-based creativity is the main factor that allows MSMEs in Bekasi City to produce innovative solutions in facing competitive business challenges. In addition, digital-based innovation provides better competitiveness in the market through the implementation of creative ideas in business practices. Digital-based marketing strategy using the 7P marketing mix: product, price, place, promotion, people, process, physical evidence on MSMEs in Bekasi city in the form of online stores in the marketplace to reach buyers in various regions and abroad. The obstacles for MSME actors in Bekasi city is that there is no team that focuses on implementing digital marketing. Efforts made by MSME actors in Bekasi city that they are actively participating in digital marketing training organized by government agencies or other parties.